An effective named entity similarity metric for comparing data from multiple sources with varying syntax. - Croft, David; Brown, Stephen; Coupland, Simon (Digital Scholarship in the Humanities, 2017)
This article describes and demonstrates a named entity similarity metric developed for, and currently in use by, the FuzzyPhoto project. The presented metric is effective at comparing named entity data in and across syntaxless data schemas such as are often encountered in Gallery, Library, Archive, and Museum collections. The efficiency of the approach was compared to an existing named entity similarity metric and is shown to be a significant improvement when comparing messy named entity data.